Immunosuppression in Cervical Cancer with Special Reference to Arginase Activity (2014)
ABSTRACT: Introduction: Cervical cancer is characterized by an immunosuppressive microenvironment and a Th2-type cytokine profile. Expression of arginase (ASE), the enzyme that converts L-arginine into L-ornithine and urea, is stimulated by Th2-type cytokines. Objective: To assess the association of ASE activity and L-Arg metabolism products with cervical cancer. Methods: Sera of 87 and 41 women with histologically confirmed by colposcopy-directed biopsy SCC and CIN3 respectively and 79 with normal cytology or Low-Grade Squamous Intraepithelial Lesion (LSIL), were evaluated. Cytokines were measured using Milliplex Human cytokine/chemokine kit. Arginase (ASE) activity was determined using an enzymatic assay. Levels of L-arginine, L ornithine, putrescine and spermine were determined by HPLC. Results: Significantly higher levels of ASE activity were observed in women with CIN3 (age-adjusted OR: 24.3; 95%CI: 3.82–155) and SCC (AOR: 9.8; 95%CI: 2.34–40.8). As expected, possibly due to high levels of ASE activity, higher levels of L-Arg were negatively associated with CIN3 (AOR: 0.03; 95%CI: 0.004–0.19) and SSC (AOR: 0.06; 95%CI: 0.02–0.24). Consistent with the role of ASE in the conversion of L-arginine to L-ornithine and polyamine production therefrom, women with cervical cancer had higher levels of spermine and putrescine. A correlation analysis revealed a significant albeit weak relationship between high levels of IL-10 and high levels of ASE (Pearson r = 0.32, p-value = 0.003) in women with cervical cancer. Conclusion: This study indicates that ASE activity and L-Arg degradation mechanisms of immunosuppression are present in cervical cancer. The results foster research in the design of possible strategies to inhibit ASE activity for therapy of cervical cancer.